2000
DOI: 10.14430/arctic873
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean Habitat Selection in the Alaskan Arctic during Summer and Autumn

Abstract: ABSTRACT. Ten years of sighting data from aerial surveys offshore of northern Alaska were analyzed to investigate seasonal variability in cetacean habitat selection. Distinct habitats were described for bowhead whales (Balaena mysticetus), white whales (Delphinapterus leucas), and gray whales (Eschrichtius robustus) on the basis of habitat selection ratios calculated for bathymetric and ice cover regimes. In summer, bowheads selected continental slope waters and moderate ice conditions; white whales selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
119
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 43 publications
8
119
0
Order By: Relevance
“…It is common in the pelagic zone, at ice edges and also the epontic zone (the area near the undersurface of ice) where it preys upon fauna in the ice algae community (Bradstreet and Cross 1982;Bradstreet et al 1986;Crawford andJorgenson 1990, 1993;Gradinger et al 2005). Physical irregularities at the ice edge may represent cryptic habitat for these Wsh, places where they can hide from a wide variety of predators (Bradstreet and Cross 1982;Lønne and Gulliksen 1989;Moore et al 2000;Gradinger and Bluhm 2004). Early life stages are predominantly in layers of zooplankton drifting beneath the ice and in open water (Sekerak 1982;Bradstreet et al 1986;Crawford and Jorgenson 1990;Fortier et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common in the pelagic zone, at ice edges and also the epontic zone (the area near the undersurface of ice) where it preys upon fauna in the ice algae community (Bradstreet and Cross 1982;Bradstreet et al 1986;Crawford andJorgenson 1990, 1993;Gradinger et al 2005). Physical irregularities at the ice edge may represent cryptic habitat for these Wsh, places where they can hide from a wide variety of predators (Bradstreet and Cross 1982;Lønne and Gulliksen 1989;Moore et al 2000;Gradinger and Bluhm 2004). Early life stages are predominantly in layers of zooplankton drifting beneath the ice and in open water (Sekerak 1982;Bradstreet et al 1986;Crawford and Jorgenson 1990;Fortier et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Because beluga feed primarily on polar cod (Bradstreet et al 1986), their feeding areas indicate the location of concentrations of the Wsh (Harwood and Smith 2002). Aerial surveys Xown in the western Arctic during September in the 1980s and 1990s yielded sightings of belugas on the outer portion of the Mackenzie Shelf and on (Clarke et al 1993;Moore et al 2000;Richard et al 2001). More recent studies monitoring movements of tagged belugas also showed them following the slope region (Richard et al 2001) where we detected Wsh near the bottom (200-350 m).…”
mentioning
confidence: 99%
“…The U.S. Department of the Interior has sponsored spring and fall aerial surveys of bowhead whales in the Beaufort Sea for monitoring purposes since 1979 (Treacy, 2002), and the present research is considered a follow-up to previous work (Moore and Clarke, 1992;Moore and Reeves, 1993;Moore and DeMaster, 1997;Moore, 2000;Moore et al, 2000). One goal of the current monitoring project is to describe distribution and movement patterns of bowhead whales in the fall, when they migrate westward across the Alaskan Beaufort Sea.…”
Section: Introductionmentioning
confidence: 93%
“…Here, we include analysis of offshore distance of bowhead whales encountered during fall surveys and describe the pattern of bowhead distribution as a function of annual sea-ice conditions. The extensive aerial survey database that we analyzed overlaps somewhat that analyzed by Moore (2000), Moore et al (2000), and others (1982 -91), but our analysis includes more recent information (1992 -2000) and an alternative interpretation of the data.…”
Section: Introductionmentioning
confidence: 99%
“…Beluga whales (Delphinapterus leucas) spend part of the summer in the Chukchi Sea, though most migrate through the Chukchi to summering areas that are located to the east (Carroll et al, 1987;Moore et al, , 2000. Similarly, bowhead whales, for the most part, migrate through the Chukchi Sea with little or no feeding in spring.…”
Section: Standing Stocks Of Marine Mammalsmentioning
confidence: 99%